Factors affecting the roles of reactive species in the degradation of micropollutants by the UV/chlorine process. (1st December 2017) - Wu, Zihao; Guo, Kaiheng; Fang, Jingyun; Yang, Xueqin; Xiao, Hong; Hou, Shaodong; Kong, Xiujuan; Shang, Chii; Yang, Xin; Meng, Fangang; Chen, Liwei
Abstract: The UV/chlorine process is an emerging advanced oxidation process (AOP) that produces various reactive species, such as hydroxyl radicals (HO ) and reactive chlorine species (RCS). The effects of the treatment conditions, such as chlorine dosage and pH, and the water matrix components of natural organic matter (NOM), alkalinity, ammonia and halides, on the kinetics and reactive species in the degradation of four micropollutants, metronidazole (MDZ), nalidixic acid (NDA), diethyltoluamide (DEET) and caffeine (CAF), by the UV/chlorine process were investigated. The degradation of MDZ and CAF was primarily attributable to HO and ClO, respectively, while that of NDA was primarily attributable to both ClO and CO3 - . HO, Cl and CO3 − are important for the degradation of DEET. The second-order rate constants for ClO with CAF and CO3 − with NDA were determined to be 5.1 (±0.2) × 10 7  M −1 s −1 and 1.4 (±0.1) × 10 7  M −1 s −1, respectively. Increasing chlorine dosage slightly changed the contribution of HO but linearly increased that of ClO to micropollutant degradation. Increasing pH decreased the contribution of either HO or Cl but not that of ClO . Both NOM and bicarbonate decreased the contributions of HO and Cl, whereas NOM but not bicarbonate significantly decreased that of ClO . The contribution of either HO or Cl first rose and then fell as the molar ratio of ammonia to chlorine increased from 0 to 1:1, while that of ClO decreased. The co-presence of high concentrations of Cl − and Br − enhanced the contribution of ClBr − and BrCl. Graphical abstract: Image 1 Highlights: Factors affecting the roles of reactive species in the UV/chlorine process were studied. The roles of reactive species (e.g., HO, Cl, ClO and CO3 - ) are micropollutant specific. [ClO ] increased with increasing chlorine dosage, but kept unchanged with pH and bicarbonate. The presence of NH4 + increased [HO ] and [Cl ] but decreased [ClO ]. The presence of Cl − & Br − promoted the formation of ClBr - and BrCl, which were important for micropollutant removal.